The Effect of Hypertension Exercise on Blood Pressure Control in the Elderly with Hypertension in the Working Area of Kumun Health Center - Herlina, Devfi (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Hypertension is a degenerative disease that is often found in the community and often appears without symptoms.Based on WHO (World Healt Organization) data,it is known that hypertension sufferers increased from 839 million people in 2018 to 940 million people in 2018 to 940 million people 2019. Management of hypertension can be done pharmacologically and non- pharmacologically. Hypertension Gymnastics is one of the non-pharmacological therapies that can be given to hypertensive patients. The purpose of this study was to determine the effect of hypertension exercise on blood pressure control in the elderly with hypertension in the working area of the Kumun Public Health Center.This study uses a pre-experimental design with a one-group pre-test-post- test design approach. The population in this study was 159 people with hypertension in the community health center. The sample in this study was 16 respondents. Data was collected by measuring blood pressure before and after being given the hypertension exercise intervention using a sphygmomanometer clock.The results showed that before the hypertension exercise intervention was given, almost all 16 respondents had high blood pressure. After being given the hypertension exercise intervention, most of the blood pressure was normal. From the statistical test, it was obtained that the Systolic P Value was 0.000, and the Diastolic P Value was 0.001, so there was an effect of hypertension exercise on blood pressure control in the elderly with hypertension in the work area of the Kumun Public Health Center.Based on research, changes in blood pressure are influenced by the movements in hypertension exercise, so this exercise is effectively used as therapy for hypertension patients. Keywords: Hypertension, Blood Pressure, Hypertension Exercise     ABSTRAK Hipertensi merupakan salah satu penyakit degeneratif yang banyak dijumpai dimasyarakat dan sering muncul tanpa gejala. Berdasarkan data WHO (World Health Organication), diketahui bahwa penderita hipertensi meningkat dari 839 juta jiwa pada tahun 2018 menjadi 940 juta jiwa pada tahun 2019. Penatalaksanan hipertensi dapat dilakukan secara farmakologis dan nonfarmakologis. Senam Hipertensi merupakan salah satu terapi nonfarmakologis yang dapat diberikan pada pasien hipertensi. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh senam hipertensi terhadap kontrol tekanan darah pada lansia dengan hipertensi di wilayah kerja puskesmas kumun. Penelitian ini menggunakan desain pre eksperimen dengan pendekatan one grup pre test-post test design. Populasi dalam penelitian ini 159 orang penderita hipertensi di wilayah puskesmas kumun, Sampel dalam penelitian sebanyak 16 Responden. Pengumpulan data dilakukan dengan mengukur tekanan darah saat sebelum dan sesudah diberikan intervensi senam hipertensi menggunakan sphygmomanometer clock. Hasil penelitian menunjukan sebelum diberikan intervensi senam hipertensi hampir seluruhnya sebanyak 16 responden memiliki tekanan darah tinggi. Setelah diberikan intervensi senam hipertensi sebagian besar bertekanan darah normal. Dari uji statistik diperoleh nilai Sistolik P Value sebesar 0,000 dan Diastolik P Value 0,001,maka ada pengaruh senam hipertensi terhadap kontrol tekanan darah pada lansia dengan hipertensi diwilayah kerja puskesmas kumun Berdasarkan Penelitian Berubahnya Tekana darah ini dipengaruhi oleh gerakan-gerakan yang ada dalam senam hipertensi,sehingga senam ini efektif digunakan sebagai terapi untuk pasien hipertensi. Kata Kunci: Hipertensi,Tekanan Darah, Senam Hipertensi